Trinity : a novel - Hall, Louisa, 1982- (Ecco, an imprint of HarperCollinsPublishers, 2018)
"From the acclaimed author of Speak comes a kaleidoscopic novel about Robert Oppenheimer--father of the atomic bomb--as told by seven fictional characters J. Robert Oppenheimer was a brilliant scientist, a champion of liberal causes, and a complex and often contradictory character. He loyally protected his Communist friends, only to later betray them under questioning. He repeatedly lied about love affairs. And he defended the use of the atomic bomb he helped create, before ultimately lobbying against nuclear proliferation. Through narratives that cross time and space, a set of characters bears witness to the life of Oppenheimer, from a secret service agent who tailed him in San Francisco, to the young lover of a colleague in Los Alamos, to a woman fleeing McCarthyism who knew him on St. John. As these men and women fall into the orbit of a brilliant but mercurial mind at work, all consider his complicated legacy while also uncovering deep and often unsettling truths about their own lives. In this stunning, elliptical novel, Louisa Hall has crafted a breathtaking and explosive story about the ability of the human mind to believe what it wants, about public and private tragedy, and about power and guilt. Blending science with literature and fiction with biography,Trinity asks searing questions about what it means to truly know someone, and about the secrets we keep from the world and from ourselves"--